The Influence of Personality on Personal Financial Management with the Use of Financial Technology and Financial Attitudes as Mediating Variables (Case Study of Generation Z in Padang City) - Suprianto, Iwil; Japriani, Meli; Marlina, Lilis (Indonesian Journal Publisher, 2025)
This study aims to examine the influence of personality on personal financial management with the use of financial technology and financial attitudes as mediating variables in Generation Z in Padang City. The method used is quantitative with data collection techniques through questionnaires. A sample of 100 respondents was selected from the Generation Z population. Data analysis was carried out using SmartPLS 4.0 software to test the proposed mediation model. The results showed that personality has a positive and significant effect on personal financial management mediated by the use of financial technology and financial attitudes. This finding emphasizes the importance of considering psychological and technological factors in efforts to improve financial management in the younger generation.